Effect of Deformation on Microstructure and Mechanical Properties of Medium Carbon Steel During Heat Treatment Process - Yan Peng (SpringerOpen, 2021)
Abstract The current research of the Q-P and Q-P-T process has been focused on controlling the heating temperature and holding time, or adding alloy elements into the steel to induce precipitation strengthening and improve the strength and plasticity of the steel. In this article, based on a quenching-partitioning-tempering (Q-P-T) process combined with a hot deformation technology, a deforming-quenching-partitioning-tempering (D-Q-P-T) process was applied to medium carbon steel. The effect of the heat treatment parameters on the microstructure and mechanical properties of experimental steel under deformation was studied. Through use of a scanning electron microscope (SEM), transmission electron microscopy (TEM) and tensile tests, the optimal heat treatment conditions for realizing high strength and plasticity that meet the safety requirements were obtained. The mechanism for the D-Q-P-T process to improve the strength and plasticity of experimental steel was discussed. A multiphase composite structure of lath martensite and retained austenite was obtained. Compared with the Q-P-T process, use of the D-Q-P-T process can increase the strength of steel by 57.77 MPa and the elongation by 5%. This study proposes a method to improve the strength and plasticity of steel.